The Concept of Inclusive Education in Islamic Perspective for Building Religious Moderation - Salim Wazdy (Cigarskruie: Journal of Educational and Islamic Research, 2024)
Inclusive education is crucial for fostering a learning environment that embraces diversity, including religious diversity. In Indonesia's multicultural society, Islamic-based inclusive education can promote religious moderation, mitigate conflicts, and enhance tolerance. This study examines the role of Islamic values in nurturing religious moderation through inclusive education. Employing a descriptive qualitative method and literature review, the study identifies Islamic principles of compassion, tolerance, and respect for differences as key to creating a moderate educational environment. Findings suggest that integrating Islamic values in inclusive education can enhance religious moderation in pluralistic societies. Thus, Islamic inclusive education is a strategic tool for fostering religious moderation and social harmony in Indonesia.